A Policy Framework for Economic Development and Employability for the English-speaking Communities of Quebec : Submitted to the Quebec Community Groups Network (QCGN) - Qu'anglo (2008)
Through previous research and following a number of community consultations, the QCGN had determined that there is a need for initiatives that will enable the English-speaking Communities of Quebec to work more effectively with the Government of Canada, the Government of Quebec, school boards and relevant stakeholders to more fully participate in the economy of province. Given the continuing exodus of educated and trained anglophones to seek employment opportunities elsewhere, and the difficulties faced by particular segments of the population, especially youth, visible minorities and newly arrived immigrants, who choose to seek employment and self-employment within Quebec, it was determined that an integrated and targeted approach to improve the economic development prospects of the community was required.
Keywords: Official Language Minority Community (OLMC)